Variasi berat roller sentrifugal Pada continuosly variable transmission (CTV) terhadap kinerja traksi sepeda motor - Dwi Budiana P., Made; Adi Atmika, I Ketut; Ary Subagia, IDG. (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Desember 2008)
The automotive technology especially motorcycle has been innovated to improve the handling stability and comfortably. The developing of motorcycle technology has applied automatic transmission system. The automatic transmission has systems which need acceleration handling and break control. From this concept has been done to develop automatic transmission system according to variable which said Continuously Variable Transmission (CVT) system.The purpose of this experiment is to know effect weight of roller centrifugal in speed governor to traction performance. The analysis traction performance executed matchematic model with motorcycle Nouvo, 115 cc 4 strokes as vehicle model. Parameter input of this calculation include: vehicle speed (V = 0-30 km/h, V = 40-70 km/h, dan V = 80-90 km/h), engine torque, and vehicle dynamic model behavior. For get the answer, the expriment executed with simulation mode and then appealed with expriment on straightaway level.The obtained result on simulation and expriment : for roller centrifugal with 8 gr weight will gave the maximum traction performance on low speed until the acceleration on low speed is faster than the roller centrifugal 10.2 gr or 12 gr. However the roller centrifugal with 12 gr weight will gave the highest traction performance on the high speed until the vehicle easy to faster in high speed, and for roller centrifugal 10.2 gr weight (standard) have traction performance between roller centrifugal 8 gr and 12 gr. So, the roller 8 gr give the best performance traction, because at a low speed is required high acceleration.
Keywords: CVT System, Motorcycle, Traction Performance, Simulation, Roller Sentrifugal, Speed Governor